Essential oil and thymol of ajwain as effective antioxidant agents - Gaba, J; Sharma, S; Kaur, P; Joshi, S (Journal of Spices and Aromatic Crops, 2020)
Ajwain is an essential herbal plant with many health and medicinal values. Quantitative phytochemical analysis of ajwain was carried out to determine total phenolic compounds, flavonoids, saponins and tannin content. The phytochemical contents were in the order saponins > tannins > flavonoids > phenolics. Essential oil was extracted and chromatographed for the major constituent thymol which was further characterized with spectral techniques. Further, role of essential oil of ajwain seeds and its major compound thymol for antioxidant activity in respect of total antioxidant capacity and free radical scavenging potential were worked out. Out of thymol and ajwain oil, former was found to be more effective antioxidant at all tested concentrations. Inhibition concentrations (IC50) of oil, thymol and ascorbic acid were found to be 1.87, 1.46 and 0.01 mg mL-1, respectively. Results suggest that ajwain and thymol can be used as natural substitutes to synthetic antioxidants in preservation of various food products.